Can novice physicians perform a high-quality record of a 12-lead electrocardiographic examination? Preliminary data - Czyż, Rafał; Leśkiewicz, Marcin; Czyż, Patrycja; Wudarczyk, Beata (Journal of Education, Health and Sport, 2018)
High-quality 12-lead electrocardiogram recording is one of the most important elements of the patient’s physical examination, not only in the case of chest pain. Carelessness and inaccuracy in the method of placing the electrodes on the patient’s body results in poor record quality which may affect the wrong therapeutic decisions and the possibility of exposing the patient of health or even life loss. The aim of the study was to determine the reliability of ECG electrodes placement on the patient’s body by novice physicians. The study group consisted of 53 novice physicians who carry out a postgraduate internship including 58% of female. Results were collected with the use of authorial and anonymous questionnaire where participants marked the correct position of all ECG electrodes. The correct position of the V1 electrode in the fourth right intercostal space was identified by only 19% of the respondents. Additionally, V1 and V2 were often (37.7%) incorrectly placed parasternally in the right and left second intercostal spaces. Only 2% of the study participants knew the correct position of the V3R electrode. Only 23% of participants knew the correct location of V7 lead, 15% location of V8 and 17% of V9 electrode. It is necessary to propagate the correct technique of performing a 12-lead electrocardiogram recording of the heart in group of novice physicians. More detailed and practical training is undoubtedly indicated. Critical review of training and education curricula is therefore recommended.